Improving Vocational Teachers' Data Modeling Competence through MATLAB and Python Training: : A Case Study at SMK Negeri Penerbangan Aceh - Muslimsyah Muslimsyah; Yuwaldi Away; Safrizal Razali (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
This training program aimed to enhance data modeling competencies among vocational teachers at SMK Negeri Penerbangan Aceh through intensive one-day MATLAB and Python training. Employing a pre-test/post-test design with 14 participants using 5-point Likert scale instruments, the results demonstrated significant improvements across all measured aspects. Key findings revealed the highest growth in work productivity (28.6% increase from 54.3% to 82.9%) and software mastery (25.7% increase from 42.9% to 68.6%). Cluster analysis identified three developmental patterns: (1) technical competencies (>20%), (2) tool integration (15-20%), and (3) conceptual understanding (<15%). The outcomes validate the effectiveness of hands-on, case-based training approaches while highlighting the need for advanced technical support programs. Practical implications suggest developing tiered training models for vocational teachers to address digital transformation challenges.